Identification of sdiA-regulated genes in a mouse commensal strain of Enterobacter cloacae - Sabag-Daigle, Anice; Dyszel, Jessica L.; Gonzalez, Juan F.; Ali, Mohamed M.; Ahmer, Brian M. M. (Frontiers in Cellular and Infection Microbiology, 2015)
Many bacteria determine their population density using quorum sensing. The most intensively studied mechanism of quorum sensing utilizes proteins of the LuxI family to synthesize a signaling molecule of the acylhomoserine lactone (AHL) type, and a protein of the LuxR family to bind AHL and regulate transcription. Genes regulated by quorum sensing often encode functions that are most effective when a group of bacteria are working cooperatively (e.g., luminescence, biofilm formation, host interactions). Bacteria in the Escherichia, Salmonella, Klebsiella, and Enterobacter genera do not encode an AHL synthase but they do encode an AHL receptor of the LuxR family, SdiA. Instead of detecting their own AHL synthesis, these organisms use SdiA to detect the AHLs synthesized by other bacterial species. In this study, we used a genetic screen to identify AHL-responsive genes in a commensal Enterobacter cloacae strain that was isolated from a laboratory mouse. The genes include a putative type VI secretion system, copA (a copper transporter), and fepE (extends O-antigen chain length). A new transposon mutagenesis strategy and suicide vectors were used to construct an sdiA mutant of E. cloacae. The AHL-responsiveness of all fusions was entirely sdiA-dependent, although some genes were regulated by sdiA in the absence of AHL.